Anaesthesia for awake craniotomy with the use of dexmedetomidine in combination with propofol infusion and ProSeal laryngeal mask airway - Shrestha, Gentle Sunder; Koirala, Megha; Karki, Prakash; Bista, Navindra Raj; Sedain, Gopal; Nath, Moda (Journal of Society of Anesthesiologists of Nepal, 2015)
Awake craniotomy for resection of tumour in the eloquent cortex aims to maximize tumour resection while sparing important areas of the brain. It poses several challenges to an anaesthesiologist. The goal is to provide adequate sedation, analgesia, and respiratory and haemodynamic control, but also an awake and cooperative patient for neurological testing. Here we report a case of awake craniotomy conducted safely with asleep-awake-asleep technique using dexmedetomidine infusion, scalp block and controlled ventilation with ProSeal laryngeal mask airway. Journal of Society of Anesthesiologists of Nepal 2015; 2(2): 84-86